Identifying and managing shoulder pain in competitive swimmers - O'Donnell, C. J.; Bowen, J.; Fossati, J. (The Physician and Sportsmedicine, 2005)
Shoulder pain resulting from glenohumeral instability is common among competitive swimmers. The biomechanics inherent to swimming promote muscular imbalances that stress the capsuloligamentous structures and contribute to shoulder instability. Most swimmers respond favorably to conservative treatment of rest and rehabilitation, while a small percentage may ultimately require surgical intervention. Swimmers who respond well to rehabilitation have a better prognosis for a successful return to swimming than those who require surgery. Overall, education in proper stroke and training techniques can minimize the likelihood that a competitive swimmer will experience disabling shoulder pain.